Basel III and Bank-Lending : Evidence from the United States and Europe - Ben Naceur, Sami.; Pepy, Jeremy; Roulet, Caroline (Washington, D.C. : International Monetary Fund, 2017)
Using data on commercial banks in the United States and Europe, this paper analyses the impact of the new Basel III capital and liquidity regulation on bank-lending following the 2008 financial crisis. We find that U.S. banks reinforce their risk absorption capacities when expanding their credit activities. Capital ratios have significant, negative impacts on bank-retail-and-other-lending-growth for large European banks in the context of deleveraging and the 'credit crunch' in Europe over the post-2008 financial crisis period. Additionally, liquidity indicators have positive but perverse effects on bank-lending-growth, which supports the need to consider heterogeneous banks' characteristics and behaviors when implementing new regulatory policies.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet